1976
DOI: 10.1002/1097-0142(197604)37:4<1782::aid-cncr2820370424>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Association of cadmium with renal cancer

Abstract: Sixty-four cases of renal cancer in white males were compared with controls (197 cases of nonmalignant diseases of the digestive system and 72 cases of colon cancer) for past exposures to cadmium. Controls were also white males, and were group-matched to the cases on age for the analyses. Data on the three main sources of exposure to cadmium--diet, cigarette smoking and occupation--were obtained by interview. The results showed a significant association of renal cancer with exposure to cadmium, and favored a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
4

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(64 citation statements)
references
References 17 publications
0
60
0
4
Order By: Relevance
“…Coke oven workers have also been reported to be at increased risk (20). Cadmium has been linked to an increased risk of renal cell cancer in one early study (21), but has not been associated in later, larger case-control studies or in occupational cohort investigations (1). Inorganic lead has induced renal tumors in laboratory animals, although there is no epidemiologic support for an association in humans (22).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Coke oven workers have also been reported to be at increased risk (20). Cadmium has been linked to an increased risk of renal cell cancer in one early study (21), but has not been associated in later, larger case-control studies or in occupational cohort investigations (1). Inorganic lead has induced renal tumors in laboratory animals, although there is no epidemiologic support for an association in humans (22).…”
Section: Risk Factorsmentioning
confidence: 99%
“…In rats, the number of tumors induced by dimethylnitrosamine was enhanced by subsequent treatment with CdCl2 (13). Several epidemiological studies point toward a higher frequency of tumors of exposed humans (14)(15)(16) and an increased incidence of renal cancer in smokers (17). A recent follow up of one of the studies (14) in a cadmium smelter in the United States confirmed a statistically significant excess in mortality from lung cancer (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic and experimental evidence has brought forth hypotheses on pr esumed work-related determinants of renal cell cancer. Those of primary concern are various hydrocarbon derivatives (24)(25)(26), petrochemical s and gasoline, jet fuel and other products of petroleum refining (16,(27)(28)(29); gasoline exhaust (18,30); cadmium (31); inorganic lead compounds (10,32); and asbestos (21,22,33).…”
mentioning
confidence: 99%